2014
DOI: 10.1128/jcm.03329-13
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of a Multilocus Sequence Typing Scheme for Streptococcus gallolyticus subsp. gallolyticus

Abstract: Streptococcus gallolyticus subsp. gallolyticus (formerly known as S. bovis biotype I) is a commensal of the gastrointestinal tract in animals and in up to 15% of healthy humans. Furthermore, it is a facultative pathogen that can cause infectious endocarditis, mastitis, and septicemia. The number of infections is increasing, but the transmission routes and zoonotic potential remain unknown. To assess the zoonotic potential and characterize the epidemiological structure of S. gallolyticus subsp. gallolyticus, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
40
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 40 publications
1
40
0
Order By: Relevance
“…In contrast, Dumke et al (2014) focused exclusively on Sgg from the Western hemisphere including human Sgg strains (n = 30) from Germany, USA and Belgium. They further included European animal isolates (mainly birds, cows and horses, n = 49), several Sgg strains (n = 18) from unknown sources and an environmental isolate.…”
Section: Isolation and Identification Techniquesmentioning
confidence: 96%
See 3 more Smart Citations
“…In contrast, Dumke et al (2014) focused exclusively on Sgg from the Western hemisphere including human Sgg strains (n = 30) from Germany, USA and Belgium. They further included European animal isolates (mainly birds, cows and horses, n = 49), several Sgg strains (n = 18) from unknown sources and an environmental isolate.…”
Section: Isolation and Identification Techniquesmentioning
confidence: 96%
“…Recently, multi locus sequence type (MLST) assays were developed for species of the SBSEC (Dumke et al, 2014;Shibata et al, 2014;C. Jans unpublished data).…”
Section: Isolation and Identification Techniquesmentioning
confidence: 97%
See 2 more Smart Citations
“…gallolyticus isolates from humans and animals have been described previously (8,10), including the existence of particular virulent clones with increased invasion and adherence abilities, which favor bloodstream infections (11)(12)(13). A recent multilocus sequence typing (MLST)-based study demonstrated a lack of specificity for any particular host or geographical location (10).…”
mentioning
confidence: 99%